Synthesis and Characterization of Silicon Based Anode Materials. (2017) - Ould Ely, T.; Batyrbekuly, D.; Sugurbekov, Y.; Stambekova, D.; Doherty, M.F.; Bakenov, Z.
Abstract: We have synthesized amorphous silicon-nanomaterials displaying high capacity and stable cyclability using an original organometallic approach. The method is based on the decomposition of silicon compounds 1Si-P1-U-2016 and 1Si-P2-C-2016, where silicon is bound to four atoms bearing an electron-withdrawing group on the β-position. These compounds decompose under argon at temperature below 500 °C. Scanning Electron Microscopy displays particles with size less than 50 nm, considerably smaller than the critical size above which silicon nanostructures will pulverize [1] . The nanosilicon particles, remain amorphous upon sintering under argon at 1150 °C, and crystallize only above 1400 °C in air, yielding SiO2 (Tetragonal, space group P41212 ). The silicon nanoparticles show excellent cycling performance, retaining a specific capacity of 1000 mAh g -1, and maintain more than 98% of its initial reversible capacity after 150 cycles. High specific capacity and stable cycle performance of the synthesized silicon makes it a promising anode material for lithium ion batteries